2013
DOI: 10.5897/err2012.250
|View full text |Cite
|
Sign up to set email alerts
|

The effects of basic gymnastics training integrated with physical education courses on selected motor performance variables

Abstract: The purpose of this study is the determine the influence of gymnastics training integrated with physical education courses on selected motor performance variables in seven year old girls. Subjects were divided into two groups: 1, control group (N=15, X=7.56±0.46 year old); 2, gymnastics group (N=16, X=7.60±0.50 year old). The students in the control group followed the physical education curriculum for 10 weeks. The students in the gymnastics group took gymnastics training for 10 weeks in addition to physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…It is a known fact that physical activities improve children's motor abilities (Haga, 2008). Alpkaya (2013) found a statistically significant increase in all parameters including balance in girl subject group children whose average age was 7.56 years, as a result of the study in which basic gymnastics training integrated into physical education lessons examined the effect of selected motor skills. According to this information, balance performance can be expressed as a feature that can be improved by direct balance studies or branch-specific training that requires balance.…”
Section: Discussionmentioning
confidence: 99%
“…It is a known fact that physical activities improve children's motor abilities (Haga, 2008). Alpkaya (2013) found a statistically significant increase in all parameters including balance in girl subject group children whose average age was 7.56 years, as a result of the study in which basic gymnastics training integrated into physical education lessons examined the effect of selected motor skills. According to this information, balance performance can be expressed as a feature that can be improved by direct balance studies or branch-specific training that requires balance.…”
Section: Discussionmentioning
confidence: 99%
“…Success in the implementation of the movements depends on the basic motoric features in AC (2,9,10). According to Daly, the strength has a significant effect on the performance of the AC (10).…”
Section: Conclusion and Evaluationmentioning
confidence: 99%
“…Delas et al (11) found a statistically significant difference in the balance, flexibility and strength parameters of gymnasts. While Alpkaya (2), in his work, integrated gymnastics branch with the specific training program of 7-year-old gymnastics balance, flexibility and strength have provided improvements. Kesilmiş (18) determined that there is a statistically significant difference in balance and force parameters applied to a gymnastics training program for preschool children.…”
Section: Conclusion and Evaluationmentioning
confidence: 99%
“…Χρειάζονται περισσότερες έρευνες για να προσδιοριστεί κατά πόσο οι μεταβολές στη μυϊκή δύναμη κατά την εφηβεία επηρεάζονται από την αλληλεπίδραση διαφορετικών διαδικασιών και από τα χαρακτηριστικά του τύπου των μυϊκών ινών (Housh et al, 1990) (Andersson, Sward, & Thorstensson, 1988;Bencke, Damsgaard, Saekmose, Jorgensen, & Klausen, 2002;Halin et al, 2002;Maffulli, King, & Helms, 1994). Ακόμα και βραχυπρόθεσμα, στοχευμένα προγράμματα προπόνησης ΕΓ είχαν θετικές επιδράσεις στην ανάπτυξη της στατικής και εκρηκτικής δύναμης, της ισχύος, της ταχύτητας και της μυϊκής αντοχής (Alpkaya, 2013;Trajković, Madić, Sporiš, Veljković, & Živčić-Marković, 2016). Επιπρόσθετα, υπάρχει ερευνητική υποστήριξη, ότι η αύξηση της ηλικίας και του επιπέδου ενασχόλησης και απόδοσης στην ΕΓ συσχετίζεται με τις βελτιωμένες κινητικές ικανότητες, αναφορικά με το επίπεδο φυσικής κατάστασης και τις ικανότητες συντονισμού (Sawczyn, 2000;Sawczyn, 1985;Kioumourtzoglou, Derri, Mertzanidou, & Tzetzis, 1997 (Cahalan et al, 1991;Cook, Gray, Savinar-Nogue, & Medeiros, 1987;Siatras et al, 2010;Wochatz et al, 2017;Zhou et al, 2014).…”
Section: αξιοπιστία των μετρήσεων στο ισοκινητικό δυναμόμετροunclassified